2014
DOI: 10.1063/1.4898674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interface state charges on the electrical properties of Si/SiC heterojunctions

Abstract: Electrical properties of p−-Si/n−-SiC, p-Si/n−-SiC, p+-Si/n−-SiC, and n+-Si/n−-SiC heterojunctions fabricated by using surface-activated bonding are investigated. Their flat-band voltages obtained from capacitance-voltage (C-V) measurements are found to be ∼0.92 eV, which suggests that the Fermi level should be pinned at the bonding interface. An analysis by using the charge neutral level model reveals that the C-V characteristics are sensitive to the density of interface states. The measured C-V characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…This value is in good agreement with our previously reported value obtained from the C-V results. 26) We confirmed that PR measurement is effective for determining qV th . We also confirmed that, because the two laser wavelengths in the SIPM measurements are within the linear portion in the PR spectra, the choice of wavelengths is reasonable for determining qV th .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…This value is in good agreement with our previously reported value obtained from the C-V results. 26) We confirmed that PR measurement is effective for determining qV th . We also confirmed that, because the two laser wavelengths in the SIPM measurements are within the linear portion in the PR spectra, the choice of wavelengths is reasonable for determining qV th .…”
Section: Resultssupporting
confidence: 69%
“…[17][18][19][20][21][22][23][24][25] We have fabricated p-Si=n-SiC and n-Si=n-SiC heterojunctions by SAB and found that the flat band voltage is ∼0.92 eV from current-voltage (I-V) measurements. 26) However, interface states with high densities are likely to be formed in the SAB process since dangling bonds are unveiled on sample surfaces owing to the irradiation of Ar atom beams. The impact of the interface states to the electrical properties of Si=SiC junctions has not yet been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the larger ideality factor (1.7) was obtained at the 4H-SiC/Si junction of E-up HBT, which suggests that the recombination or tunneling current dominates the electrical transport properties across the interfaces. The large number of interface states should be formed at the bonding interface according to our previous report, 15 which could act directly as trapping and recombination centers. β increased with increasing the devices temperature and the larger value was obtained at 573 K, while which is much smaller than those previously reported for 3C-SiC/Si 3 and a fluorine-doped SiC/Si 4 HBTs fabricated by the epitaxy growth and atmospheric pressure CVD reactor, respectively.…”
mentioning
confidence: 90%
“…14 Furthermore the conduction band offset and the density of interface states were estimated by analyzing the capacitance-voltage characteristics of n-SiC/p-Si and n-SiC/n-Si junctions. 15 In this work we discuss the transport properties of electrically injected minority electrons in 4H-SiC/Si HBT structures with emitter-up (E-up) and collector-up (C-up) configurations fabricated by SAB.…”
mentioning
confidence: 99%
See 1 more Smart Citation